Karakteristik Kimia Biskuit Berbahan Baku Tepung Whey untuk Penderita Autis - Fitri M Manihuruk; Zakiah Wulandari (Musamus Journal of Livestock Science, 2021)
People with autism have an allergic reaction to foods containing gluten and casein. Food processing innovation is needed. Whey powder, the by-product of cheese, have a high protein but can be consumed by people with autism safely. The objectives of this research to evaluate organoleptic and chemical characteristics of different whey powder-based biscuits to obtain the best formulation as a special food for people with autism. Biscuit formulations with the different addition of whey powder 5%, 10%, 15%, and 20% was observed organoleptic and chemical characteristics. Casein and gluten protein of the best formulation biscuit was analysed by SDS-PAGE method. The results of this research showed that the addition of whey powder had a significant difference to organoleptic characteristics, the content of ash, protein, and free fatty acid. The SDS-PAGE analysis showed that protein fraction of casein and gluten were not seen significantly with band protein standard on 5% whey powder-based biscuit.